Babel's vertigo and normalizing education (Dissertare, 2018)
Being in society implies the construction of spaces and normalizing mechanisms and homogenization of the particular, in terms of the common interest interposed intrinsically in the very act of socialization. The order is erected as the central category of this analytical-interpretative essay, from which it is intended to generate reflection on the role of education as a mechanism of containment of the forces that challenge the social order. For this purpose, Foucault's theory of power (1976) is adopted as a fundamental reference around the capital role of the educational act within the framework of power interdictions and regulations. Education is enthroned as a mechanism that models and produces socially acceptable individuals, according to the scheme of a specific order, which is expressed at all times of the social life of the individual in the suppression of any disturbing element of order. The principle of schooling in which education has derived in contemporaneity has its roots in the paideia Platonic excellent model that assigns to education the responsibility of regulating the first years of life of man, in favor of certain parameters of social order and to the detriment of the vertigo implicit in the chaos.
Keywords: order; power; socialization; normalizing education